2020
DOI: 10.1302/2046-3758.99.bjr-2020-0023.r1
|View full text |Cite
|
Sign up to set email alerts
|

Surgical site infection after hip fracture surgery

Abstract: Aims This study explores the reported rate of surgical site infection (SSI) after hip fracture surgery in published studies concerning patients treated in the UK. Methods Studies were included if they reported on SSI after any type of surgical treatment for hip fracture. Each study required a minimum of 30 days follow-up and 100 patients. Meta-analysis was undertaken using a random effects model. Heterogeneity was expressed using the I2 statistic. Risk of bias was assessed using a modified Newcastle-Ottawa Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Previous studies on NIs in elderly patients who receive surgical treatment of hip fractures have mainly focused on surgical site infections (SSI) [11]. Factors such as age [10], comorbidities [12,13], surgical methods [14], season [15], and delayed surgery [12,16,17] have been found to be related to the occurrence of SSIs.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on NIs in elderly patients who receive surgical treatment of hip fractures have mainly focused on surgical site infections (SSI) [11]. Factors such as age [10], comorbidities [12,13], surgical methods [14], season [15], and delayed surgery [12,16,17] have been found to be related to the occurrence of SSIs.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study from the UK by Masters et al ( 6 ) found an increased number of reoperations due to SSI. The study included SSI with and without operation and was based on 20 studies from 18 UK institutions with vast variations in SSI definition.…”
Section: Discussionmentioning
confidence: 96%
“…Studies have indicated an increase in SSI in primary arthroplasties over a 10-year period ( 5 ), but to our knowledge data on time-trend in reoperation due to SSI after hip fracture is lacking. A recent review from 2020 ( 6 ) found an overall incidence of 2.1% reoperation due to SSI (varying from 1% to 12%). The review included hip fracture patients from 20 studies of which most were retrospective, single-center studies, and only of UK origin, with considerable inter-study differences, including SSI definitions.…”
mentioning
confidence: 99%
“…One major complication of arthroplasty is the development of a periprosthetic joint infection (PJI), which occurs in up to 3% of the performed (partial) arthroplasties [ 7 , 8 ]. Besides a high psychological burden for patients and their families, PJI often need a two-stage revision procedure and therefore demonstrate immense socioeconomic costs for the healthcare systems [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%